2018
DOI: 10.32890/jict2018.17.2.8
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on Predictors of Green Sustainable Software Practices in Malaysian Electronic Industries

Abstract: Currently, sustainability is a pertinent issue that should be considered in the software development process; hence it is imperative to recognize how environmental-friendly practices can be applied in the electronic industries that develop and deploy software products. However, sustainability is not fully considered when electronic industries implement modern software systems. Additionally, software developers in electronic industries believe that software is environmental friendly mainly because it is virtual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Cronbach's Alpha or coefficient alpha (α) was applied to assess internal consistency. Coefficient alpha is the most adopted objective measure of reliability (Anthony et al, 2018). An acceptable α value should be higher than 0.7 (George & Mallery, 2009;Senarathna et al, 2018).…”
Section: Correlation Analysis Resultsmentioning
confidence: 99%
“…Cronbach's Alpha or coefficient alpha (α) was applied to assess internal consistency. Coefficient alpha is the most adopted objective measure of reliability (Anthony et al, 2018). An acceptable α value should be higher than 0.7 (George & Mallery, 2009;Senarathna et al, 2018).…”
Section: Correlation Analysis Resultsmentioning
confidence: 99%
“…It permits a simple perception of reconciliation and understanding of environment, social and economic issues [23]. The main and fundamental dimensions for sustainability need to be embedded as the prerequisites for sustainability and green software process [24]. Referring to sustainability in software, the economic dimension is concerned with preserving capital and value.…”
Section: Green Measurements Based On Sustainability Dimensionsmentioning
confidence: 99%
“…These IT benefits have also been identified in the previous literature such as the works by Joachim (2011) and Baskerville et al (2005) where they has identified that IT benefits is consist of reusability, integration, flexibility, agility, and scalability. Furthermore, Anthony, Majid, and Romli (2018) also mentioned that generally IT can contribute towards resolving the sustainable issues such as facilitating the Green software engineering by providing eco-logically-friendly services such as deploying virtual teleconference rather than traveling to attend it. In addition, business benefits have also been stated as important benefits that should be achieved by adopting SOA.…”
Section: Objectivementioning
confidence: 99%